Microstructure of doped barium titanate prepared from polymeric precursors - Stojanovic, B. D. [UNESP]; Foschini, C. R. [UNESP]; Zaghete, M. A. [UNESP]; Cilense, M. [UNESP]; Varela, José Arana [UNESP] (Elsevier, 2002)
Barium titanate is used extensively as a dielectric in ceramic capacitors, particularly due to its high dielectric constant and low dielectric loss characteristics. It can be made semiconducting by addition of certain dopants and by proper modification of grains and grain boundary properties obtaining very interesting characteristics for various applications. The synthesis method and sintering regime have a strong influence on properties of obtained barium titanate ceramics. Doped barium titanate was prepared with Nb+5 and Y+3 ions as donor dopants, and with Mn+2 ions as acceptor dopant by polymeric precursors method. By this procedure nanosized powders were obtained after calcination. Sintering was performed in the temperature range of 1290°C to 1380°C The microstructure of doped BaTiO3 was performed using scanning electron microscopy. The influence of dopants and sintering temperature on grain size was analysed.
Keywords: Barium titanate; Doping; Grain size; Microstructure; Polymeric precursors; SEM